Recruitment Policies, Job-Filling Rates and Matching Efficiency - Carlos Carrillo-Tudela; Hermann Gartner; Leo Kaas (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Recruitment behavior is important for the matching process in the labor market. Using unique linked survey-administrative data, we explore the relationships between hiring and recruitment policies. Faster hiring goes along with higher search effort, lower hiring standards and more generous wages. To analyze the mechanisms behind these patterns, we develop a directed search model in which firms use different recruitment margins in response to productivity shocks. The calibrated model points to an important role of hiring standards for matching efficiency and for the impact of labor market policy, whereas search effort and wage policies play only a minor role.
Keywords: E24; J23; J63; 330; vacancies; recruitment; labor market matching